Evaluating the Impact of CrossFit on Sambo Athletes: A 10-Week Intervention Study with Statistical Insights and Future Directions (GYMNASIUM, 2025)
This study investigates the effects of a 10-week CrossFit training program on the physical fitness of sambo athletes, focusing on strength, endurance, agility, and reaction speed. Twentyone athletes, aged 18-24, were divided into two groups: a control group continuing their traditional training and an experimental group completing CrossFit three times a week. Both groups underwent 8 performance tests assessing general and special fitness, strength, endurance, and agility, before and after the intervention. Statistically significant improvements (p < 0.05) were observed in three out of eight tests for the experimental group, specifically in abdominal strength (p
Keywords: CrossFit training, sambo athletes, performance assessment, 10-week intervention, strength